Sosialisasi Pengenalan dan Pemilahan Sampah pada Siswa MA DDI Alliritengae - Irma Sakti; Fitriani Kadir; Reski Idamayanti; Napsawati Napsawati (PPM LP2M UIN Alauddin Makassar, 2022)
One important factor in maintaining the cleanliness of the school environment is student awareness in disposing of trash. The concept of waste management needs to be instilled in students to form behavior and self-awareness to maintain a clean and healthy environment. The partners involved in this Community Service activity are students at MA DDI Alliritengngae Maros. The solution offered is socialization to students to recognize waste, sort waste, and dispose of waste in the space provided. The output produced through this activity is that students can recognize and sort organic waste, inorganic waste, B3 waste.